The Effect of Message Framing on African American Women's Intention to Participate in Health-Related Research. Issue 5 (3rd May 2016) - Balls-Berry, Joyce E.; Hayes, Sharonne; Parker, Monica; Halyard, Michele; Enders, Felicity; Albertie, Monica; Pinn, Vivian; Radecki Breitkopf, Carmen
Abstract : This study examined the effect of message framing on African American women's intention to participate in health-related research and actual registration in ResearchMatch (RM), a disease-neutral, national volunteer research registry. A community-engaged approach was used involving collaboration between an academic medical center and a volunteer service organization formed by professional women of color. A self-administered survey that contained an embedded message framing manipulation was distributed to more than 2, 000 African American women attending the 2012 national assembly of The Links, Incorporated. A total of 391 surveys were completed (381 after exclusion: 187 containing the gain-framed message and 194 containing the loss-framed message). The majority (57%) of women expressed favorable intentions to participate in health-related research, and 21% subsequently enrolled in RM. The effect of message framing on intention was moderated by self-efficacy. There was no effect of message framing on RM registration; however, those with high self-efficacy were more than 2 times as likely as those with low self-efficacy to register as a potential study volunteer in RM (odds ratio = 2.62, 95% confidence interval [1.29, 5.33]). This investigation makes theoretical and practical contributions to the field of health communication and informs future strategies to meaningfully and effectively include women and minorities in health-related research.